The immune-microbiome axis in salt-sensitive hypertension: a focus on renal and neural mechanisms - Cardoso, Leonardo Máximo; Wainford, Richard David (Frontiers in Physiology, 2025)
Systemic arterial hypertension (SAH) is a prevalent condition affecting humans and other mammals, with high salt intake recognized as a major risk factor for its development and progression. This review examines the intricate interplay between dietary salt, immune signaling, neural regulation and renal mechanisms in the pathophysiology of salt-sensitive hypertension (SSH). High salt consumption not only directly influences blood pressure but also induces low-grade inflammation by activating both innate and adaptive immune responses, particularly promoting pro-inflammatory T cell (TH17/IL-17) and macrophage phenotypes. These immune alterations impact key organs involved in blood pressure regulation, including the kidneys and central nervous system (CNS). In the CNS, salt-induced immune activation, especially microglial activation and cytokine production in regions such as the paraventricular nucleus, enhances sympathetic outflow and contributes to neurogenic hypertension. Disruption of the blood-brain barrier further facilitates immune cell infiltration and perpetuates neuroinflammation. Additionally, recent evidence shows that high salt intake alters the gut microbiome, reducing its diversity and favoring pro-inflammatory bacterial populations, which further amplify immune dysregulation via the gut-grain axis. The role of the kidneys in sodium handling is modulated by immune cell infiltration and cytokine-drive changes in sodium channel expression, reinforcing salt sensitivity. Aging and sex differences further modulate these pathways, increasing SSH risk in older individuals and postmenopausal women. Emerging therapeutic strategies targeting the gut microbiota, immune signaling, and neural pathways offer promise improvement for SAH management. However, further research is needed to clarify causal mechanisms and optimize interventions that address the neural-immune-microbiome axis in hypertension.